2021
DOI: 10.1186/s12877-021-02591-2
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a multicomponent intervention on functional capacity and independence on activities of daily living in individuals with neurocognitive disorder

Abstract: Background To examine the effects of a 6-month multicomponent (MT) exercise intervention in the functional capacity and ability to independently perform activities of daily living (ADL) of individuals diagnosed with neurocognitive disorder (NCD). Methods A quasi-experimental controlled trial with a parallel design study was conducted in multicentered community-based settings. Forty-three individuals (N Female: 30) were allocated to an exercise grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Previous studies attested MT effectiveness in improving individuals with NCD lower body function, 30,31 gait speed and mobility. 30,39 However, less evidence has been shown on the effects of MT physical exercise interventions on psychosocial outcomes. [40][41][42] Previous meta-analytic and systematic review studies indicated that physical exercise interventions might improve cognitive function, or slow down the decline in individuals with major NCD; still, findings have been inconsistent across studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies attested MT effectiveness in improving individuals with NCD lower body function, 30,31 gait speed and mobility. 30,39 However, less evidence has been shown on the effects of MT physical exercise interventions on psychosocial outcomes. [40][41][42] Previous meta-analytic and systematic review studies indicated that physical exercise interventions might improve cognitive function, or slow down the decline in individuals with major NCD; still, findings have been inconsistent across studies.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study suggest that a 6-month MT physical exercise intervention was not effective in improving cognitive function, neuropsychiatric symptomatology, and quality of life of older adults diagnosed with major NCD. Previous studies attested MT effectiveness in improving individuals with NCD lower body function, 30 , 31 gait speed and mobility. 30 , 39 However, less evidence has been shown on the effects of MT physical exercise interventions on psychosocial outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of physical activity (PA), specifically exercise, as a nonpharmaceutical approach to prevent, delay, or reverse the course of NCD have been extensively explored. [1][2][3] A large body of evidence highlights the potential benefits of PA and exercise on cognitive function, [4][5][6] ability to independently perform activities of daily living (ADL), 7 functional capacity, 8,9 and physical fitness 10 in individuals with NCD. Yet, this population is reported to be highly sedentary, and the small amount of PA they perform tends to be of lower intensity when compared with their healthy peers.…”
Section: Introductionmentioning
confidence: 99%